Re-imagining China’s future: Soft power, cultural presence and the East Asian media market - Keane, Michael (Monash University ePress, 2010)
This chapter provides an overview of cultural exchange in China during the imperial period (221 BC- 1911 AD). The discussion begins with a discussion of three development trajectories which I call territory, technology and taste. The second section examines the effects of taste in more detail through examples of China’s creativity in art, philosophy and technology. The principal argument is that while China’s cultural authority was established on deep Confucian roots, its international influence, and its creativity, is indebted to periods of openness to ideas. The chapter concludes with an examination of China’s ’soft power’ rhetoric, itself a response to recent acknowledgements of China’s ’cultural trade deficit’. The chapter asks if China can claim ’soft power’ and cultural authority in East Asia.